Functional outcomes after modified Sauve-Kapandji arthrodesis for distal radioulnar joint dysfunction - Seenappa, Hiranya Kumar; Mittemari, Karthik Narayanamurthy; Nadagouda, Shivaraj; Nimmagadda, Vamshikrishna Chand (International Journal of Research in Orthopaedics, 2021)
Background: The distal radioulnar joint (DRUJ) dysfunction manifests as pain, weakness and reduced range of motion. There are various treatments for DRUJ dysfunction. Modified Sauvé-Kapandji procedure involves arthrodesis of the distal radioulnar joint combined with the creation of a pseudarthrosis of the distal ulna to maintain forearm pronation and supination, and stabilization of proximal ulnar stump. This study was performed to evaluate the clinical outcomes of modified Sauve-Kapandji procedure for patients with DRUJ dysfunction. Methods: Fourteen patients with DRUJ dysfunction were treated by modified Sauve-Kapandji procedure and followed up for 2 years post-operatively. Functional assessment was evaluated according to modified mayo wrist score (MMWS) system and severity of pain by visual analog scale. Posteroanterior and lateral radiographs were used to assess fusion. Results: There was a significant improvement in VAS of wrist pain (p<0.001) and MMWS (p<0.001) at 2 years follow up. Excellent outcome was reported in 64.3% (n=9) patients. Radiographic fusion was seen in all 14 cases. Conclusions: The modified Sauve-Kapandji procedure for DRUJ dysfunction is a safe and effective procedure with excellent radiological fusion and significant improvement in functional outcomes.